The SEM Concept: Style, Environment, Meaning - Rappaport, Alexander (project baikal, 2021)
In architectural science, the topic of environment has been widely discussed for more than half a century without much effect. The topic of style was displaced from the architectural science as early as in the 1970s, on the one hand, by the environmental approach, and by postmodernism on the other. Environment seemed to be a category opposing the style. A new, deeper understanding of the style implies bringing it closer to environmental phenomena. The style is normative. Meaning can move freely from the normative to the incidental. All this brings meaning closer to the environment, which is equally subjective and spontaneous.
Keywords: style; environment; environmental approach; meaning; form